New insights into tomato microRNAs - Cardoso, Thaís Cunha de Sousa (Sci Rep, 2018)
Cultivated tomato, Solanum lycopersicum, is one of the most common fruits in the global food industry. Together with the wild tomato Solanum pennellii, it is widely used for developing better cultivars. MicroRNAs affect mRNA regulation, inhibiting its translation and/or promoting its degradation. Important proteins involved in these processes are ARGONAUTE and DICER. This study aimed to identify and characterize the genes involved in the miRNA processing pathway, miRNA molecules and target genes in both species. We validated the presence of pathway genes and miRNA in different NGS libraries and 6 miRNA families using quantitative RT-PCR. We identified 71 putative proteins in S. lycopersicum and 108 in S. pennellii likely involved in small RNAs processing. Of these, 29 and 32 participate in miRNA processing pathways, respectively. We identified 343 mature miRNAs, 226 pre-miRNAs in 87 families, including 192 miRNAs, which were not previously identified, belonging to 38 new families in S. lycopersicum. In S. pennellii, we found 388 mature miRNAs and 234 pre-miRNAs contained in 85 families. All miRNAs found in S. pennellii were unpublished, being identified for the first time in our study. Furthermore, we identified 2471 and 3462 different miRNA target in S. lycopersicum and S. pennellii, respectively.